Community-Based Disaster Management: A Case Study of Tani Siaga in Pagar Dewa Village - Haerul Jamal; Andhita Tarnatania Hidayat; Mohamad Adli; Isa Elfianto; Rifky Amri Amrullah; M. Nurtian Passabena (Indonesian Journal of Social Responsibility Review (IJSRR), 2025)
Pagar Dewa Village faces the threat of forest and land fires (karhutla) due to prolonged droughts, while the government's capacity for disaster management remains limited in terms of access and resources. PT Perusahaan Gas Negara Tbk established Tani Siaga through its Corporate Social and Environmental Responsibility (TJSL) program to enhance community-based disaster preparedness and mitigation. This study employs a qualitative method with a case study approach on the Tani Siaga group in Pagar Dewa Village. Data collection was conducted through observation, interviews, and document analysis. The findings indicate that PGN Pagardewa Station's community-based disaster management implementation includes disaster risk analysis using the REA method, program planning, training and education, provision of infrastructure and facilities, awareness campaigns, monitoring and evaluation, and an exit strategy. This program has successfully improved community preparedness for karhutla, strengthened coordination with the village government and PGN, and encouraged active participation in disaster prevention. Furthermore, support for productive enterprises among Tani Siaga members has contributed to the program's sustainability and the economic empowerment of the community.